y-2(y-3)+4=

Simple and best practice solution for y-2(y-3)+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-2(y-3)+4= equation:


Simplifying
y + -2(y + -3) + 4 = 0

Reorder the terms:
y + -2(-3 + y) + 4 = 0
y + (-3 * -2 + y * -2) + 4 = 0
y + (6 + -2y) + 4 = 0

Reorder the terms:
6 + 4 + y + -2y = 0

Combine like terms: 6 + 4 = 10
10 + y + -2y = 0

Combine like terms: y + -2y = -1y
10 + -1y = 0

Solving
10 + -1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -1y = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -1y = 0 + -10
-1y = 0 + -10

Combine like terms: 0 + -10 = -10
-1y = -10

Divide each side by '-1'.
y = 10

Simplifying
y = 10

See similar equations:

| 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 |

Equations solver categories